Osteotropism of Breast and Prostate Cancer: Clinical and Experimental Perspective - Manuel Scimeca#; Francesca Starace#; Deborah Gratti; Viviana Benedicta Sapia; Rita Bonfi glio; Elena Bonanno (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2017)
Breast and prostate cancer are the two most common invasive cancers in women and men, respectively. Although these cancers arise in organs that are different in terms of structure and function, both organs require sexual hormones for their development, and tumors that arise from them are typically hormone-dependent and have extraordinary affinity each other [1]. That breast and prostate cancer share several biological, genetic and epidemiological aspects is known since 1950s. Pioneering studies designed to ascertain the genetic bases of breast cancer detected a higher frequency of prostate cancer among the relatives of women with breast cancer, which led them to propose that prostate cancer could be the male equivalent of at least some female mammary carcinomas [2].